Design and Build a Student Value Processing Information System (eRapor): (Case study: SMKN 1 Kecamatan Luak) - Dewi, Ika Parma; Ambiyar , Ambiyar; Riyanda, Afif Rahman; Fadilla, Reva; Adi, Novi Hendri (Politeknik Ganesha Medan, 2022)
SMK Negeri 1 Kecamatan Luak is a government agency that organizes vocational education. Every semester SMK Negeri 1 Luak Regency does data processing of student scores, but in processing student grades they still use the manual system, namely by collecting assignment scores, test scores, mid-semester test scores and end-semester test scores. The exam is then processed by the subject teacher, then the score is submitted to the administrative staff, after that the administrative staff submits all student scores to the homeroom teacher to be entered into leger paper which is then processed into report cards. This is considered less effective, causing a lot of time and energy needed in the process of processing student grades. Facilitate the process of processing student scores to become e-reports at SMK Negeri 1 Luak District. With the information system for processing student grades at SMK Negeri 1 Luak District, it helps process student grades into report cards and ledgers easily, quickly and precisely. In addition, in a pandemic situation, the information system processing student grades data is very helpful for submitting semester report cards to students and their parents in order to avoid crowds to prevent transmission of the Covid-19 virus. This application is designed using the System Development Life Cycle (SDLC) method, in developing the SDLC the author uses the waterfall method in designing information systems.